Patellar tendon versus artificial grafts in anterior cruciate ligament reconstruction: a systematic review and meta-analysis - DingYuan Fan; Jia Ma; Lei Zhang (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The aim of anterior cruciate ligament reconstruction (ACLR) is to restore the function of the knee joint, protect the cartilage, and reduce the occurrence of osteoarthritis. However, due to the structural limitations of the human body, it is not possible to perform ACLR with conventional sutures. To restore normal functioning of the anterior cruciate ligament (ACL), a new ligament must be reconstructed in the position of the previous ACL. Objective To compare autografts and synthetic grafts in terms of postoperative knee stability and function Search methods The protocol for this study was registered with PROSPERO (CRD42021243451). Two reviewers independently searched the PubMed, Embase, and the Cochrane Library databases from database inception though February 10, 2021. The following search method was used: ((Autograft) OR (Autologous) OR (Autotransplant)) OR Artificial Ligament AND (Anterior Cruciate Ligament Injury [MeSH Terms]) AND (Randomized controlled trial [MeSH Terms]). Methodological quality was assessed by the Cochrane risk of bias tool. Selection criteria We only included randomized controlled trials (level I) that compared autograft and synthetic graft interventions in participants with ACL injury. We included trials that evaluated ACLR using at least one outcome (Lachman test, pivot shift test, IKDC grades, or complications). Results A total of 748 studies were identified in the initial literature search, and seven studies that examined only bone-patellar tendon-bone (BPTB) grafts compared with artificial grafts met the predetermined inclusion criteria. The results showed that BPTB grafts were associated with significantly better pivot shift test and Lachman test results and better IKDC grades and lower complication rates than synthetic grafts. Conclusions This review indicates that for adults, BPTB grafts perform more favorably than synthetic grafts in ACLR in terms of knee stability, function, and complication. More research is needed to compare autologous tendons and allogeneic tendons with artificial ligaments, especially in elderly individuals. Level of evidence Level I, systematic review and meta-analysis